Differences in physiological traits associated with water balance among rodents, and their relationship to tolerance of habitat fragmentation - Castellar, Alexandre [UNESP]; Bertoli, Paula Custódio [UNESP]; Galdino, Leonardo Henrique [UNESP]; Domeniconi, Raquel Fantin [UNESP]; Cruz-Neto, Ariovaldo Pereira [UNESP] (Wiley-Blackwell, 2015)
Physiological concepts and tools can help us to understand why organisms and populations respond to habitat fragmentation in the way they do, and allow us to determine the mechanisms or individual characteristics underlying this differential sensitivity. Here, we examine food intake, relative medullary thickness and distribution/expression of water channel aquaporin-1 in three species of South American rodents that have been reported to have different levels of tolerance to habitat fragmentation (Akodon montensis, Oligoryzomys nigripes, and Euryoryzomys russatus), using a classic water deprivation experiment to assess their abilities to cope with water shortage. We believe the mechanisms underlying this differential sensitivity are related to the organisms' capacities to maintain water balance, and therefore the species more tolerant to habitat fragmentation (A. montensis and O. nigripes) should have a higher capacity to maintain water balance. We found that A. montensis and O. nigripes were more tolerant to water deprivation than E. russatus, and this difference appears to be unrelated to differences in food ingestion rate. O. nigripes showed the highest values for RMT, followed by A. montensis and E. russatus. However all species showed RMT values that were 2.2% to 14.1% below the lower prediction limit when compared to other rodents through allometric relationships. Water deprivation seems to trigger changes in the distribution of aquaporin-1, mostly for O. nigripes and E. russatus, which may contribute to water balance maintenance. Our data suggest that these intrinsic physiological differences among these species could provide a mechanism for their differential tolerance of habitat fragmentation. J. Exp. Zool. 9999A:XX-XX, 2015. © 2015 Wiley Periodicals, Inc.